Insights of red cell distribution width for mortality in septic patients with diabetes mellitus: A multicenter cohort study - Kunsheng Zhao; Guang Zhang; Chengsheng Wu; Dawei Wang; Hongyu Zhang (PLoS ONE, 2025)
The correlation between red cell distribution width (RDW)and mortality in septic patients with diabetes mellitus has not been extensively investigated. This study aimed to explore the correlation between RDW and mortality and potential value of RDW as a prognostic indicator in septic patients with diabetes mellitus. A total of 5476 septic patients with diabetes mellitus were included in this multicenter retrospective cohort study. Multivariate logistic regression, dose-response, and mediation analyses were conducted to examine the association between RDW and mortality in septic patients with diabetes mellitus. The predictive value of RDW was assessed using the receiver operating characteristic (ROC) curve analysis and SHapley Additive exPlanations (SHAP) analysis. The improvement in the model was assessed using net reclassification improvement (NRI) and integrated discrimination improvement (IDI). After adjusting for all confounders, RDW was an independent variable for mortality (odds ratio [OR]: 1.37, 95% confidence interval [CI]: 1.26, 1.50, per standard deviation in RDW, P < 0.001). Moreover, RDW was positively correlated with 28-day mortality in a non-linear manner. The contribution of the predictive value of RDW was substantial in the ROC curve and SHAP analyses. The addition of RDW improved the predictive performance of the baseline model (continuous NRI [95% CI], 0.284 (0.188, 0.379); P < 0.001; IDI [95% CI], 0.012 (0.007, 0.016); P < 0.001). In conclusion, RDW may be a valuable indicator for predicting risk stratification and outcomes in septic patients with diabetes mellitus.